APLIKASI GAME EDUKASI PEMBELAJARAN SENI BUDAYA MENGGUNAKAN LINEAR CONGRUENTIAL GENERATOR (LCG) - Ahmad Thariq; Mita Paramitha (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
Cultural arts have several types. One of them that has developed in Maluku for generations is traditional music. The lack of knowledge of students about the introduction of traditional music is partly due to limited facilities and lack of cultural arts learning hours at school. The existence of this research aims to create an innovative educational game for learning cultural arts that is more modern by utilizing smartphone technology. Making this educational game will use the MDLC (multimedia development life cycle) model using the C# programming language and unity 3D as software. In addition to displaying some material about learning cultural arts, in this case the introduction of Maluku traditional musical instruments in the application there is also a quiz that displays 10 randomized questions with a total of 20 questions. The method used in randomizing questions is linear congruential generator (LCG). By utilizing a linear congruential generator (LCG) can produce randomized question numbers so that students have questions with different numbers and the learning process at SD Negeri 9 Namlea becomes more effective. This application can be a learning media for students at SD Negeri 9 Namlea, because it provides cultural arts learning information about the types of traditional musical instruments in Maluku and is equipped with a quiz that can be played by the user.